The spider genus Hersilia in Thailand, with descriptions of two new species (Araneae, Hersiliidae) - Dankittipakul P. (2014)
Our examination of a hersiliid spider collection from Thailand revealed eight species of which two species are new (Hersilia serrata sp. n. ♂, ♀, H. thailandica sp. n., ♂). Extended geographic ranges are recorded for H. sundaica Baehr & Baehr, 1993 and H. martensi Baehr & Baehr, 1993, which are reported from Thailand for the first time. H. asiatica Song & Zheng, 1982, which was previously documented from northeastern Thailand, is now also found in northern and southern Thailand. A substantial number of females from Thailand are similar to H. striata Wang & Yin, 1985, previously known from China, but can be distinguished by slight differences in their genital morphology.